A general electrochemical strategy for upcycling polyester plastics into added-value chemicals by a CuCo2O4 catalyst. Issue 17 (15th August 2022) - Liu, Fulai; Gao, Xutao; Shi, Rui; Tse, Edmund C. M.; Chen, Yong
Abstract : A general and efficient electro-reforming strategy was demonstrated to selectively convert polyester plastics into added-value chemicals at the anode catalyzed by a CuCo2 O4 /Ni foamcatalyst while generating H2 at the cathode under mild conditions. Abstract : The recycling of plastic waste is one of the most urgent issues in the 21 st century owing to its detrimental impact on the environment and human health. However, it is greatly challenging to develop more efficient, low-cost and general methods capable of selectively converting plastic waste into added-value and separable chemicals while restricting their distribution. Here, we report a general electrocatalytic strategy for the selective upcycling of various polyester plastics into added-value chemicals by a CuCo2 O4 /Ni foam catalyst under mild conditions. In particular, polyethylene terephthalate (PET) was upcycled into terephthalate and formate with high efficiency and selectivity (>86%) even at a high current density of 100 mA cm −2 . The electrocatalytic reaction mechanism was thoroughly elucidated by electrochemical in situ FTIR, NMR and DFT calculations. This work not only develops a superior electrocatalyst for upcycling various polyester plastics, but also provides guidance for the design of new and efficient electrocatalysts.